1974
DOI: 10.1063/1.1663228
|View full text |Cite
|
Sign up to set email alerts
|

Titanium impurity center induced in irradiated silicate glasses

Abstract: The induced ESR spectra in silicate glasses is examined with particular emphasis on the reported ESR line centered at g -1.96. This resonance is shown to arise from an induced center associated with titanium which is present in the glass as a trace impurity. The optical absorption band corresponding to this center was observed, at 2.4 eV, in the Gaussian resolution of the induced optical absorption spectrum. It is argued that the interpretation of induced ESR and optical absorption spectra in silicate glasses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…For example, S. Arafa and F. Assagbhy [26] observed in X-irradiated SiO 2 -Na 2 O-TiO 2 glasses an EPR spectrum characterized by g / =1.9693 and g // =1.9413 very similar to our s I spectrum. H. Böhm and G. Bayer [29] also obtained a similar spectrum defined by g / =1.970 and g // =1.930 by studying the [VI] Ti 3+ formed under reducing atmosphere in Mg 2 TiO 4 crystals.…”
Section: Simulation Of Experimental Ti 3+ Epr Spectrasupporting
confidence: 74%
See 1 more Smart Citation
“…For example, S. Arafa and F. Assagbhy [26] observed in X-irradiated SiO 2 -Na 2 O-TiO 2 glasses an EPR spectrum characterized by g / =1.9693 and g // =1.9413 very similar to our s I spectrum. H. Böhm and G. Bayer [29] also obtained a similar spectrum defined by g / =1.970 and g // =1.930 by studying the [VI] Ti 3+ formed under reducing atmosphere in Mg 2 TiO 4 crystals.…”
Section: Simulation Of Experimental Ti 3+ Epr Spectrasupporting
confidence: 74%
“…These spectra are complex and may be separated into two groups of lines. The first group, centered around g=2.0076± 0.003 and close to the g-value of free electron (g e =2.0023 [22]) is attributed to the paramagnetic hole defects created by irradiation [5,7] and the second group, centered around g=1.935±0.003 is attributed to Ti 3+ ions [22,25,26]. In this paper we will mainly focus our study on the EPR spectrum of Ti 3+ ions.…”
Section: Simulation Of Epr Spectramentioning
confidence: 99%
“…The first result associated to this work is that the s I site is encountered in both silicate and ABS glass compositions showing therefore the lack of influence of other network formers (B 3+ , Al 3+ ) on s I EPR parameters. According to literature [13,14], the s I site EPR parameters reveal an octahedral environment around Ti 3+ ions. By contrary, the presence of boron and aluminum ions in network formers position influences the EPR parameters of s II and s III sites leading to b II and b III , respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The other EPR signal at g = 1.934 was found to be due to Ti+ 3 centers by a combined EPR/optical absorption spectroscopy study [6]. It was found that the Ti+ 3 centers are partly responsible for the absorption at 2.6 eV, which is a characteristic crystal field splitting energy of Ti+ 3 ions in many materials [10]. In order to show that the optically induced Pb+ 3 and Ti+ 3 centers are only a feature of the perovskite structure, we now investigate the response of UV-illumination on the (1) diphasic (pyrochlore and perovskite) and (2) Table I.…”
Section: (Degrees)mentioning
confidence: 95%